2020
DOI: 10.1101/2020.07.15.20154237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic performance and prediction of clinical progression of plasma phospho-tau181 in the Alzheimer’s Disease Neuroimaging Initiative

Abstract: Whilst cerebrospinal fluid (CSF) and positron emission tomography (PET) biomarkers for amyloid-beta and tau pathologies are accurate for the diagnosis of Alzheimer's disease (AD), their broad implementation in clinical and trial settings are restricted by high cost and limited accessibility. Plasma phosphorylated-tau181 (p-tau181) is a promising blood-based biomarker that is specific for AD, correlates with cerebral amyloid-beta and tau pathology, and predicts future cognitive decline. In this study, we report… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
87
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 50 publications
(107 citation statements)
references
References 43 publications
16
87
2
2
Order By: Relevance
“…We found that plasma p-tau181 was higher in males and in APOE ε4 carriers, which to our knowledge is a nding that has not been yet described. We also observed plasma p-tau181 to be signi cantly associated with older age, fewer years of education, elevated global cortical composite measure of Aβ-PET, and worse performance on cognitive scores, which, with the exception of education, concur with earlier studies on plasma p-tau181 [9][10][11][12]28]. As previously described, in our cross-sectional analyses, plasma p-tau181 was correlated with CSF p-tau181.…”
Section: Discussionsupporting
confidence: 92%
“…We found that plasma p-tau181 was higher in males and in APOE ε4 carriers, which to our knowledge is a nding that has not been yet described. We also observed plasma p-tau181 to be signi cantly associated with older age, fewer years of education, elevated global cortical composite measure of Aβ-PET, and worse performance on cognitive scores, which, with the exception of education, concur with earlier studies on plasma p-tau181 [9][10][11][12]28]. As previously described, in our cross-sectional analyses, plasma p-tau181 was correlated with CSF p-tau181.…”
Section: Discussionsupporting
confidence: 92%
“…We observed a signi cant contribution of plasma p-tau181 independently of APOE ε4 in this model. Previous studies investigating the association of plasma p-tau181 with AD, either did not consider the APOE genotype (13,12); or they did not consider the effects of this factor independently of p-tau181 (10,9). Considering the APOE ε4 genotype as a covariate, we found that plasma p-tau181 additionally contributes to improve the prediction of AD in patients with cognitive impairment.…”
Section: Associations Of Plasma Nfl and P-tau181 With Disease Severitcontrasting
confidence: 56%
“…Plasma p-tau181 has been recently reported to be increased in both clinically diagnosed (9) and biomarker con rmed AD dementia (10), and to correlate with CSF tau levels and amyloid PET measurements (11,12). Furthermore, it may predict disease progression and cognitive decline in cognitively unimpaired participants and MCI patients (13).…”
Section: Introductionmentioning
confidence: 98%
“…Nine studies that used Simoa or MSD methods were included for the analysis of normal range of plasma ptau181. Six publications, reporting seven cohorts, were retrieved using the Simoa technology [45,[84][85][86][87][88], including 1424 healthy subjects. The ES for plasma ptau181 levels in healthy populations was 11.18 pg/ml (95% CI 9.68-12.68, I 2 = 95.9%, P < 0.0001, Fig.…”
Section: Study Inclusions and Quality Assessmentmentioning
confidence: 99%